2011
DOI: 10.1016/j.quascirev.2010.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation context and climatic limits of the Early Pleistocene hominin dispersal in Europe

Abstract: a b s t r a c tThe vegetation and the climatic context in which the first hominins entered and dispersed in Europe during the Early Pleistocene are reconstructed, using literature review and a new climatic simulation. Both in situ fauna and in situ pollen at the twelve early hominin sites under consideration indicate the occurrence of open landscapes: grasslands or forested steppes. The presence of ancient hominins (Homo of the erectus group) in Europe is only possible at the transition from glacial to intergl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 57 publications
1
48
0
2
Order By: Relevance
“…present). However, recent studies revealed that only minor climatic oscillations have occurred since 9 ka BP (Leroy et al, 2011). Thus, coatings from O Pindo could have ages younger than this last age.…”
Section: Discussionmentioning
confidence: 99%
“…present). However, recent studies revealed that only minor climatic oscillations have occurred since 9 ka BP (Leroy et al, 2011). Thus, coatings from O Pindo could have ages younger than this last age.…”
Section: Discussionmentioning
confidence: 99%
“…1.4-1.2 Ma; Palmqvist et al, 2005;Carbonell et al, 2008;Martínez-Navarro et al, 2010). In the Iberian Peninsula, this time interval was characterized by warm temperatures and no great climatic shifts, with landscapes dominated by open dry grasslands and several wooded areas (Leroy et al, 2011). Several authors suggested that the paleoenvironmental conditions most favorable for the dispersal of hominins across Europe would correspond to open landscapes, similar to the African environments where early Homo had evolved.…”
Section: Iberian Late Villafranchian/early Galerian Carnivorans and Ementioning
confidence: 99%
“…This signifies that small, controlled, campfires were most probably used for warmth in combination with cave-dwelling while the retainment and the growth of more body hair over time, also figure into that equation. This is even whenever any journeys up to the far north experienced a limited timewindow of interglacial conditions (Leroy et al, 2011) which still would have seen low temperatures, although not as low as when it was under full glacial conditions. Yet, Dennell (2012) claims that hominins such as H. erectus of Dmanisi, did not have to endure cold temperatures because he assumed that they only settled into their mid-latitude environment (at latitude 41° N) during the summer months followed by their evacuation from Dmanisi when cold temperatures arrived.…”
Section: Adaptation To Low Paleo-temperatures and Different Paleo-envmentioning
confidence: 99%